Donor-site Chyle Leakage after Breast Reconstruction Using a Deep Inferior Epigastric Artery Perforator Flap. Issue 10 (19th October 2022) - Nakatsuka, Kengo; Karakawa, Ryo; Fuse, Yuma; Yoshimatsu, Hidehiko; Yano, Tomoyuki
Abstract : Summary: Postoperative chyle leakage is an uncommon type of lymphorrhea characterized by a milky white lymphatic fluid. Here, we report a case of postoperative donor-site chyle leakage after breast reconstruction using a deep inferior epigastric artery perforator (DIEP) flap. A 50-year-old woman underwent unilateral secondary breast reconstruction using a DIEP flap. On postoperative day (POD) 3, 50 mL of clear white liquid was observed in the abdominal suction drain over 12 hours. On POD 6, the amount of white-colored fluid in the left side suction drain increased to 190 mL/d with high triglyceride 674 mg/dL. The computed tomography scan showed no fluid collections intraabdominally, within the rectus abdominis muscle, or in the subcutaneous area. Based on the diagnosis of donor-site subcutaneous chyle leakage, the patient was treated with a low-fat diet, a medium-chain triglyceride diet, and compression of the contralateral groin area. The fluid became clear and decreased in quantity, and we removed the drain on POD 9. No abdominal fluid was observed after the discharge. Combined treatment with a low-fat diet and compression of the groin area may be effective for donor-site chyle leakage after breast reconstruction using the DIEP flap.